2015
DOI: 10.3389/fmicb.2015.00939
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric evaluation of physico-chemical impact on Gram-positive and Gram-negative bacteria

Abstract: Since heat sensitivity of fruits and vegetables limits the application of thermal inactivation processes, new emerging inactivation technologies have to be established to fulfill the requirements of food safety without affecting the produce quality. The efficiency of inactivation treatments has to be ensured and monitored. Monitoring of inactivation effects is commonly performed using traditional cultivation methods which have the disadvantage of the time span needed to obtain results. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
2
20
0
Order By: Relevance
“…The use of cell impermeable dye, propidium iodine, where fluorescence increases when the membranes are disrupted, indicated that treatment with He and He-N 2 for 10 min with one hour post storage resulted in complete membrane disruption (TO + PI + ), which is not the case for He-O 2 plasma treatment which resulted in only injured cells with no membrane disruption but cell depolarization (TO + PI int ), less staining for thiazole orange. Our results are in line with other studies [ 29 , 42 44 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The use of cell impermeable dye, propidium iodine, where fluorescence increases when the membranes are disrupted, indicated that treatment with He and He-N 2 for 10 min with one hour post storage resulted in complete membrane disruption (TO + PI + ), which is not the case for He-O 2 plasma treatment which resulted in only injured cells with no membrane disruption but cell depolarization (TO + PI int ), less staining for thiazole orange. Our results are in line with other studies [ 29 , 42 44 ].…”
Section: Resultssupporting
confidence: 94%
“…Flow cytometry analyzis confirmed these datas. Simultaneous staining with thiazole orange (TO) and propidium iodide (PI) allows the distinction of live (TO + PI − ), dead (TO + PI + ) with total membrane disruption, and injured (TO + PI int ) cell populations, a viable but non-culturable VBNC form with no total membrane disruption [ 42 ]. The results showed that the population within the grey circle (TO + PI − ) ( Fig 1E ), which refers to bacteria with high membrane potential disappeared regardless of the applied plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation mechanism of NTP is still unclear. However, three mechanisms are usually proposed: UV radiations of genetic material, photodesorption of cell by UV radiations and etching by ions and chemical reactive species ( Moisan et al, 2001 , 2002 ; De Geyter and Morent, 2012 ; Fröhling and Schlüter, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-thermal plasma is an ionized gas consisting of UV-VUV photons, charged particles, reactive species (e.g., reactive oxygen species – ROS, OH., O 2 , 1 O 2 - ; reactive nitrogen species – RNS, NO ∙ , ONOO ∙ , …), excited molecules (e.g., excited O 2 , N 2 , …) depending on the plasma process and the gas nature ( Moisan et al, 2001 ; Laroussi and Leipold, 2004 ; Gaunt et al, 2006 ; Liao et al, 2017 ). Nowadays there are numerous NTP techniques such as corona discharge, electric barrier discharge, microwave discharge or plasma jet that can inactivate various bacterial strains ( Lerouge et al, 2001 ; Moisan et al, 2001 ; Boscariol et al, 2008 ; Sureshkumar et al, 2010 ; Fröhling et al, 2012 ; Kvam et al, 2012 ; Alkawareek et al, 2014 ; Fröhling and Schlüter, 2015 ; Scholtz et al, 2015 ; Impe et al, 2018 ). These technologies differ from each other in terms of electrical current, discharge reactor designs, working pressures, and operating conditions (nature and flow rate of the gas).…”
Section: Introductionmentioning
confidence: 99%